Pelatihan Desain Kemasan Produk dan Media Pemasaran Online UMKM di Kelurahan Kukusan, Kota Depok - Soni Trison; Shafira Nurfadhila; Achmad Ali Badjrai; Adefia Fahira; Muhammad Adil Mutaqqin; Muzdhalifah Razalina; Sheva Rezki Ramadhan; Muhammad Naufal Shidqi; Axelshan Zaki Shahputra; Widya Purnama Sari; Ragita Diaz Astiza (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The coronavirus pandemic (COVID-19) is a problem that is being faced by more than 200countries around the world. Depok City is one of the cities in Indonesia that has been the worstaffected by COVID-19. The impact of this pandemic is not only on the health and social sectorsbut also in the economic sector of the community, especially for owners of Micro, Small andMedium Enterprises (MSMEs). Thematic-Based Service Learning Program (SLP????T) IPB helpedMSMEs in Kukusan Village, Depok City, which were affected by the pandemic, to increase salesof MSME products by holding training on product packaging design and online marketing.Training on the theme of "Appropriate Use of Packaging", "Packaging Design", and "OnlineMarketing Strategy" was held with an online approach through the Whatsapp Group applicationand an offline approach with interviews and direct practice with selected MSMEs. Overall,Kukusan MSMEs already has good product quality, it just requires stronger branding to increasesales. With this training, MSME players can increase the attractiveness of their packaging andexpand product marketing. The training that has been carried out has provided benefits to MSMEsin Kukusan Village. Keywords: MSMEs, training, design, packaging, marketing